EFL First Year Students’ Writing Problems and Proposed Remedial Strategies The Case of 1st Year University Students at the English Department University of Biskra - Bouhitem, Tayeb (Sciences humaines; Vol. 29 (2013): SCIENCES HUMAINES, 2014)
من المؤسف إنها لكارثة، أتمنى أن أجد و لو جملة صحيحة في تعبيرهم الكتابي و لكن من هو المسئول على ذلك؟ و ما هو الحل؟ هذا ما يطرحه أساتذة قسم الانجليزية في اجتماعاتهم البيداغوجية من أسئلة. أجري هذا البحث على 80 طالبا مقسمين إلى فوجين من قسم الانجليزية – جامعة محمد خيضر - بسكرة. حيث يتطرق البحث إلى المشاكل و العوائق التي يواجهها الطلبة أثناء التعبير الكتابي باللغة الإنجليزية. إن نتائج البحث تؤكد أن إخفاق الطلبة في التعبير الكتابي أسبابه الرئيسية راجعة إلى أولا: الجانب اللغوي (ضعف الكفاءة اللغوية لدى الطلبة). ثانيا: الجانب البيداغوجي (عدم نجاعة طرق تدريس التعبير الكتابي). و هذا ما يؤدي إلى لامبالاة الطلبة و نزوحهم عن الكتابة. حيث يسلط الضوء على الأسباب الحقيقية الكامنة وراء هذا الإخفاق و اقتراح بعض الاستراتيجيات الناجعة في تدريس التعبير الكتابي لدى طلبة الجامعة و تحسين كفاءتهم الكتابية.   It‘s a pity, it is terrible, I hope I could only find one single grammatically correct sentence in their writing; they know nothing, who is to blame?: Or who is the responsible for this? How to overcome this; I do not know. This is what teachers at Mohamed Kheider University (MKU) English Department talk about in their departmental meetings. The participants were 80 first year students at the Department of English university of Biskra and concerns 2 classes of 40 students each. The present study seeks to explore EFL learners’ major writing problems and to try to find out the main causes that hinder the development of students’ writing competence .The results of the study indicate that learners’ failure in writing is mostly caused by linguistic(students poor linguistic competence) and psycho-pedagogical problems (inappropriate teaching methodology) and this leads to psychological problem ‘(learners’demotivation) or students’ lack of interest .The remedial strategies were suggested so that teachers can apply or adopt them to enhance students’ writing proficiency at tertiary level in Algeria. Key Words: error analysis, writing problems, remedial strategies.